Coaching disadvantaged young people: Evidence from firm level data - Jens Mohrenweiser; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
In Germany, apprenticeship training firms currently face a shrinking number of qualified school-leavers because of smaller birth cohorts and an increasing proportion of school leavers aiming for higher education. This paper investigates whether a programme that supports firms to train disadvantaged youth can reduce recruiting difficulties in apprentice training firms. Based on unique firm-level data from the metal and electronic industry in Baden-Württemberg from 2010 to 2013, we apply instrumental variable and difference-in-difference estimations and find no significant short-term causal impact of the programme.
urn:nbn:de:bsz:180-madoc-370326
Keywords: J11; J24; M51; L60; 330; disadvantaged youth; apprenticeship training; programme evaluation